Toxicity of Copper (Cu) and Chromium (Cr) on the Seed Germination of Mung Bean (Vigna radiata L.) - Astuti, Sutan Nur Chamida Tri; Nugroho, Andhika Puspito (Universitas Ahmad Dahlan, 2022)
Rapid industrial growth may have implications for an increase in cases of pollution of soil ecosystems through untreated waste disposal. Copper and chromium are metals found in some types of industrial wastewater, such as electroplating and silversmithing, that are essential at low concentrations but toxic at high concentrations. Vigna radiata was chosen as the test organism because it has been reported that the yield and production of the crop have decreased worldwide due to heavy metal pollution. This study aims to evaluate individual and mixed Cu and Cr toxicity in the seed germination of V. radiata. The individual and mixed Cu and Cr toxicity test was started with a range-finding and definitive test for 96 h. The toxicity level of the individual metal was expressed as IC50-96 h by probit analysis. For the mixed test, the organism was exposed to concentration ratios of Cu and Cr: 10%:90%; 35%:65%; 50%:50%; 65%:35%; and 90%:10% of individual IC50-96 h, each conducted for 96 h. The results showed that the individual IC50-96 h of Cu was 127.4 mg/L, while for Cr, it was 615.23 mg/L, indicating that Cu is more toxic than Cr. The mixed test showed that the IC50-96 h of Cu was 247.5 mg/L, 579.85 mg/L for Cr. The highest inhibition value at the mixed test was at a Cu and Cr concentration ratio of 90%:10%. Based on the mixed test, the interaction of Cu and Cr resulted in an additive effect (CI=1).